Sanksi Adat Penyelesaian Kasus Pelecehan Seksual di Desa Kungkai Kabupaten Merangin Jambi - Anggi Purnama Harahap; Devrian Ali Putra; Ardian Kurniawan; Muhammad Aiman (Wajah Hukum, 2022)
The threat of criminal sanctions in Indonesian state law does not have a major impact on reducing sexual harassment cases. In some places, efforts to sanction cases of sexual harassment using adat law can be another alternative, because of the unique relationship between traditional communities and adat law. This research examines the existence and implementation of adat law sanctions to solve the problem of sexual harassment in Kungkai Village, Merangin, Jambi Province. The type research is field research or empirical juridical research using a legal anthropological approach. The data collection instrument is through observation, interviews with indigenous peoples, and literature review. Adat sanctions for perpetrators of sexual harassment crimes in Kungkai Village are called “utang adat”. This sanction was given by the adat party in Kungkai Village for perpetrators of sexual crimes to pay compensation. The application of Islamic values in the Jambi Malay traditional seloko, adat bersendi syarak, syarak bersendi Kitabullah can be found from the addition of punishment by assessing the marital status of the perpetrator or victim such as the jarimah zina in Islamic criminal law. The existence of adat law has an urgency to maintain community compliance with legal values and norms.